PERSEPSI MAHASISWA FAKULTAS ILMU KEOLAHRAGAAN PRODI PGPJSD ANGKATAN 2009 UNIVERSITAS NEGERI SEMARANG TERHADAP PRESTASI SEPAK BOLA TIMNAS INDONESIA DARI TINGKATAN JUNIOR SAMPAI SENIOR (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study to determine how far the department of sport science faculty students of 2009 class PGPJSD semarang domestic universities understand the achievements of football in Indonesia. This study uses descriptive quantitative approach, meaning the procedure or how to solve the problem by describing the percentage of results obtained. The samples in this study were 105 students but 4 is not active college students (move / leave) and one student as a researcher. This study uses a sampling technique that is total sampling, where all respondents in this study as the research object. Scatterplot data collection using questionnaires and documentation. The data analysis technique used is descriptive statistical techniques. Indonesian football management is undergoing a split between PSSI and KPSI who have a desire in each camp to fight on their own. Disagreements between the stronghold of PSSI and KPSI and arrogance within each management makes management relations became strained. So frequent disagreements can not be resolved properly and cause a desire to stand alone in their management. Studies conclusion that the decline in the performance of Indonesian football that has the most impact is in terms of management that caused the dispute two camps of Indonesian football management.